The Effect of Ratio of Sorbitol Concentration with Purple Sweet Potato Juice and Carrageenan Concentration on the Quality of Jelly Candy - Derta Sari; Sentosa Ginting; Zulkifli Lubis (Universitas Sumatera Utara, 2016)
The aim of the research was to find the effect of ratio of concentration of sorbitol with purple sweet potato juice and carrageenan concentration on the quality of jelly candy. The research was using completely randomized design with two factors, i.e ratio of concentration of sorbitol with Purple sweet potato Juice (S): (50%:50%, 60%:40%, 70%:30%, 80%:20%) and carrageenan concentration (K): (1%, 2%, 3%, 4%). The results showed the that ratio of concentration of sorbitol with purple sweet potato juice had highly significant effect on moisture content, vitamin C content, total acid content, total soluble solid content, ash content, value color of L, value color of a, value color of b, hedonic values of color, taste, texture, and scores of texture. The concentration of carrageenan had highly significant effect on total acid content, ash content, value color of L, value color of a, and had significant effect on organoleptic scores value of texture. Interaction of the two factors had highly significant effect on total acid content, ash content, and had significant effect on total soluble solid content, and scores value of texture. The ratio of concentration of sorbitol with purple sweet potato juice of 60%:40% (S2) or carrageenan concentration of 3% (K3) produced the best jelly candy. The best product reducing sugar was 4,2625% and the amount of antioxidant activity (IC50 value) was 187,6699 ppm. Keywords: carrageenan, jelly candy, purple sweet potato juice, sorbitol.